GANTI RUGI KEBAKARAN HUTAN AKIBAT PEMBUKAAN LAHAN KELAPA SAWIT (STUDI PUTUSAN NOMOR 171/PDT/G/2020/PN.JKT.PST): Compensation For Forest Fires Due to Oil Palm Land Clearing (Study of Decision Number 171/PDT/G/2020/PN.JKT.PST) - Fendry Aliffia Putri Yusendhi; Irene Mariane (Faculty of Law, Universitas Trisakti, 2024)
Indonesia is an agrarian country. Indonesia's forests are very large, but now there is a lot of forest destruction such as forest fires. The formulation of the problem is whether the amount of compensation for forest fires due to land clearing based on decision number 171/Pdt/G/2020/PN.Jkt.Pst is in accordance with the Forestry Law? and how is the analysis of forest fire law enforcement in decision number 171/Pdt/G/2020/PN Jkt.Pst?. It is normative legal research, descriptive analytical. Using secondary data. Analyzed qualitatively by drawing conclusions deductively. The result and conclusion is that the amount of compensation for forest fires due to land clearing based on Decision Number 171/Pdt/G/2020/PN.Jkt.Pst is in accordance with the Forestry Law. Article 7 paragraph (1) letter b of PERMENLHK Number 7 of 2014 which contains this provision to carry out and determine the calculation of the amount of compensation that must be paid by the Defendant. After the calculation, it was decided that the amount of compensation to be paid by the Defendant was Rp.160,530,895,240,-. The enforcement of forest fire laws in this Decision is still inappropriate because of the sanctions regarding forest fires, namely the provisions of Article 78 paragraph (3) jo Article 80 the Forestry Law.